Metadata analysis of the squalene epoxidase gene in dermatophytes - Ismail, Fatima; Ahmad, Iqra; Javed, Eqaza (International Journal of Endorsing Health Science Research, 2021)
Background: Squalene epoxidase gene is an azole antifungal target enzyme in the ergosterol biosynthesis pathway in fungi—the inhibition of enzyme aggregate squalene, a type of ergosterol derivative depletion that leads to fungal growth inhibition. Squalene epoxidase widely diverges in three fungal groups of dermatophytes Trichophyton, Microsporum and Epidermophyton. Methodology: The study has demonstrated a variety of squalene epoxidase genes in the dermatophyte genome. Squalene epoxidase gene was also studied for possible single nucleotide polymorphism (SNPs) in the Trichophyton group's homologs and found multiple SNP positions that induce non-synonymous mutation and change the sequence of amino acid into protein structure that can change phenylalanine to leucine. Results: Squalene epoxidase is widely present in dermatophytes. Mutation in the squalene epoxidase gene can mislead normal sterol formation in the fungal cell membrane that induces fungal resistance against several drugs, including azoles and polyenes. Squalene epoxidase gene carries 2 - 3 transcripts and 2 - 3 number of exons. Squalene epoxidase gene has FAD-dependent oxidoreductases and NADP binding domain conserved domains in fungal groups of dermatophytes. Conclusion: This study analyzed the abundance of the squalene epoxidase gene, suggesting that squalene epoxidase gene-resistant mutants can occur naturally. Thus squalene epoxidase gene should be extensively studied in order to increase the potential of available antifungals.